18F-PSMA-1007 salivary gland dosimetry: comparison between different methods for dose calculation and assessment of inter- and intra-patient variability. (21st April 2023) - Pistone, Daniele; Gnesin, Silvano; Auditore, Lucrezia; Italiano, Antonio; Cascini, Giuseppe Lucio; Amato, Ernesto; Cicone, Francesco
Abstract: Objective . Simplified calculation approaches and geometries are usually adopted for salivary glands (SGs) dosimetry. Our aims were (i) to compare different dosimetry methods to calculate SGs absorbed doses (ADs) following [ 18 F]-PSMA-1007 injection, and (ii) to assess the AD variation across patients and single SG components. Approach. Five patients with prostate cancer underwent sequential positron-emission tomography/computed tomography (PET/CT) acquisitions of the head and neck, 0.5, 2 and 4 h after [ 18 F]-PSMA-1007 injection. Parotid and submandibular glands were segmented on CT to derive SGs volumes and masses, while PET images were used to derive Time-Integrated Activity Coefficients. Average ADs to single SG components or total SG (tSG) were calculated with the following methods: (i) direct Monte Carlo simulation with GATE/GEANT4 considering radioactivity in the entire PET/CT field-of-view (MC) or in the SGs only (MCsgo); (ii) spherical model (SM) of OLINDA/EXM 2.1, adopting either patient-specific or standard ICRP89 organ masses (SMstd); (iii) ellipsoidal model (EM); (iv) MIRD approach with organ S -factors from OLINDA/EXM 2.1 and OpenDose collaboration, with or without contribution from cross irradiation originating outside the SGs. The maximum percent AD difference across SG components ( δ max ) and across patients (Δmax ) were calculated. Main results . Compared to MC, ADs to single SG components were significantly underestimated by all methods (average relative differences ranging between −11.9% and −30.5%). δ max values were never below 25%. The highest δ max (=702%) was obtained with SMstd. Concerning tSG, results within 10% of the MC were obtained only if cross-irradiation from the remainder of the body or from the remainder of the head was accounted for. The Δmax ranged between 58% and 78% across patients. Significance . Simple geometrical models for SG dosimetry considerably underestimated ADs compared to MC, particularly if neglecting cross-irradiation from neighboring regions. Specific masses of single SG components should always be considered given their large intra- and inter-patient variability.